Evaluation of foraminal transportation during foraminal enlargement with different instrumentation systems - Diogo Silva; Aline Cristine Gomes; Juliana Melo da Silva; Aline de Almeida Neves; Alexandre Augusto Zaia; Emmanuel João Nogueira Leal da Silva (Universidade Estadual de Campinas, 2014)
Aim: To evaluate the foraminal transportation during foraminal enlargement after manual instrumentation with stainless steel files, preparation with the Mtwo system and Reciproc R25 file. Methods: Thirty roots were selected, divided in three groups and prepared in accordance with the different instrumentation systems: Hand Files (HF); Mtwo system (MS); and Reciproc system (RS). All groups were prepared with the instrumentation level 1 mm beyond the apex. Photomicrographs were performed using scanning electron microscopy, to record the foraminal anatomy before and after instrumentation. Data were analyzed using ANOVA followed by Tukey's test with a significance level of 5%. Results: The group instrumented with hand files showed higher foraminal transportation when compared to the Mtwo and Reciproc groups (p<0.05). Reciproc group showed lower transportation when compared to the Mtwo group (p<0.05). Conclusions: The stainless steel files caused significant foraminal transportation, while Reciproc system showed safe apical preparation, with little transportation.